The Importance of Early Initiation of Prenatal Care: A Case Report - Bilinski, Valéria Ronsom; Cracco, Eduarda Fanhani; Marin, Maria Clara; Nickenig, Luiza Maria; Heleno, Helena Almada; de Sousa, Renam Arthur (Brazilian Journal of Case Reports, 2025)
Accurate determination of gestational age is essential for proper prenatal care management, directly impacting maternal and fetal health. This study addresses the importance of a detailed medical history and thorough physical examination in estimating gestational age. The patient was initially classified as being in an early gestational stage; however, due to the absence of a meticulous clinical examination, the actual gestational age was underestimated. The case highlights the need for a complementary diagnostic approach when clinical uncertainties arise, ensuring more accurate follow-up. Early recognition of pregnancy and correct estimation of gestational age are crucial to reducing complications and improving maternal-fetal outcomes. Therefore, this study aims to reinforce the importance of early physical examination and the support of complementary investigations.